Educational intervention to prevent postoperative complications and improve functional outcomes in patients with transurethral resection of the prostate - Parvez, Mohd.; Kalal, Nipin; Singh, Dr. Mahendra; Sharma, Khina (Investigación y Educación en Enfermería, 2025)
Objective. To assess the effectiveness of an educational intervention in reducing post-operative complications and improve functional outcome patients undergoing Transurethral Resection of the Prostate -TURP-. Methods. A quasi-experimental nursing-led study (post-test only control design) was conducted among 60 TURP patients (intervention group n=30 and control group n=30). Face-to-face education on self-management strategies lasting 20-25 minutes, educational booklet and weekly telephone follow-up was administered to the intervention group; while control group received routine care. Data collection tool administered at 4th and 8th week post TURP included a post-operative checklist, IPSS (International Prostate Symptom Score), and IIEF (international index of erectile function). Results. Urinary incontinence rates were considerably reduced in the experimental group at 4 weeks (p<0.001). Despite an 8-week reduction in differences, both groups Indicated effective care and no cases of trans-urethral resection syndrome or urinary tract infection. In the experimental group, IPSS scores were lower (9.9±4.6) than in the control group (15.6±5.8) indicating improved symptoms (p<0.001). Additionally, IIEF scores were higher in the experimental Group (3.5±1.2) than in the control group (2.6±1.2), suggesting improved erectile function with nurse-led intervention (p<0.004). Conclusion. The nurse-led educational intervention effectively improves functional outcomes and reduce post-operative complications in Benign prostatic hyperplasia patients following TURP. Integrating such interventions by healthcare professionals can further accelerate recovery and minimize complications.